Forecasting The Financial Soundness Of Indonesia’s National Board Of Zakat (baznas) Using Artificial Neural Network Models - Syamsuri Syamsuri; Fuadah Johari; Nadhilah Nadhilah; Yaumi Sa’adah (UIKTEN - Association for Information Communication, 2024)
Indexed by Scopus